In vitro Evaluation of the Anti-hypercholesterolemic Effect of Lactobacillus Isolates From Various Sources - Tjandrawinata, Raymond Rubianto; Kartawijaya, Medicia; Hartanti, Apriliana Wahyu (Frontiers in Microbiology, 2022)
The anti-hypercholesterolemic effect of 11 Lactobacillus isolates was investigated in vitro by measuring remaining cholesterol in growth media, growing ability in media supplemented with cholesterol, and BSH activity. Amongst the selected isolates, DLBSH104, DLBSH122, and DLBSK207 have demonstrated outstanding potential as cholesterol-lowering cultures. The three isolates showed high cholesterol removal by growing cells, whereas resting and dead cells showed less cholesterol removal. Furthermore, visualization of those isolates in growing and non-growing states by SEM showed the ability of DLBSH104 to attach cholesterol to their cell surface. In contrast, alteration of DLBSH122 and DLBSK207 cells did not involve surface attachment of cholesterol. Thus, the isolates' ability to remove cholesterol is mainly attributed to the cells' metabolically active state that assimilates and incorporates cholesterol into the cell membrane as reflected by a significantly higher cholesterol removal in a growing state than a non-growing state. Only in DLBSH104, cholesterol removal also involves attachment on the cell surface. Moreover, DLBSH104 has beneficially affected the host cell by a significant reduction of NPC1L1 mRNA levels that are responsible for intestinal cholesterol absorption. In hepatic cells, cell-free supernatant (CFS) from DLBSH104 and DLBSK207 were able to reduce LDLR and HMGCR mRNA at the transcription level. To sum up, L. helveticus DLBSH104 and L. plantarum DLBSK207 are confirmed as isolates with anti-hypercholesterolemic effect.